2013
DOI: 10.1091/mbc.e13-07-0357
|View full text |Cite
|
Sign up to set email alerts
|

Wnt5a signaling promotes apical and basolateral polarization of single epithelial cells

Abstract: Wnt signal plays important roles in polarization. Here intestinal epithelial cells are shown to form apicobasal polarization at a single-cell level in an extracellular matrix adhesion–dependent manner. Wnt5a signaling promotes single-cell polarization through balanced control between Rac1 and RhoA activities spatially.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 49 publications
1
26
0
Order By: Relevance
“…In keeping with the association of Wnt5a signaling with actin dynamics and organelle movements (12)(13)(14)22), we questioned whether the detrimental effect of Wnt5a on parasites internalized by macrophages could result, at least in part, from Wnt5a-induced alterations in cytoskeletal dynamics. Given that the Rac1/Rho family GTPases are Wnt5a signaling intermediates (16,17,21), we rationalized that Wnt5a-Rac1/Rho-mediated changes in the cytoskeletal actin organization and associated NOX activity (23)(24)(25)(26) could restrict the formation and sustainment of PVs crucial for parasite survival in macrophages (12)(13)(14)37).…”
Section: Wnt5a-rac1/rho Gtpase-mediated Altered Cytoskeletal Dynamicsmentioning
confidence: 98%
“…In keeping with the association of Wnt5a signaling with actin dynamics and organelle movements (12)(13)(14)22), we questioned whether the detrimental effect of Wnt5a on parasites internalized by macrophages could result, at least in part, from Wnt5a-induced alterations in cytoskeletal dynamics. Given that the Rac1/Rho family GTPases are Wnt5a signaling intermediates (16,17,21), we rationalized that Wnt5a-Rac1/Rho-mediated changes in the cytoskeletal actin organization and associated NOX activity (23)(24)(25)(26) could restrict the formation and sustainment of PVs crucial for parasite survival in macrophages (12)(13)(14)37).…”
Section: Wnt5a-rac1/rho Gtpase-mediated Altered Cytoskeletal Dynamicsmentioning
confidence: 98%
“…Because Wnt5a stimulation correlates with Rac1 activity (9,23,24,27), we investigated whether the homeostatic Wnt5a arbitrated basal NF-kB activity in macrophages with concurrent CD14 expression is Rac1 dependent. Initially, we confirmed that Wnt5a-depleted macrophages harbor reduced levels of basally activated Rac1 by demonstrating an ∼50% reduced level of GTP-gS bound Rac1 in the Wnt5A siRNA-transfected RAW264.7 macrophages compared with the corresponding controls (Fig.…”
Section: Wnt5a-nf-kb-cd14 Axis In Macrophages Is Rac1 Dependentmentioning
confidence: 99%
“…The cytoplasmic adapter protein disheveled (Dvl), is crucial for both b-catenin2dependent and independent Wnt5a signaling (16-18, 23, 24). Contemporary research highlights how different cellular proteins orchestrate Dvl function (23,24). However, the precise biochemical mechanisms of Dvl coupling to the steady state versus activated conformations of ligand-receptor combinations of Wnt5a-Fz/ROR in different cell types are not completely understood.…”
mentioning
confidence: 99%
“…The central inductive cue(s) that drives non-muscle myosin II activation during gastrulation is constituted by Wnt signaling [200,265]. This function of Wnt seems to be conserved during later development [268] and among animals: Wnt signaling can cell-autonomously modulate actomyosin distribution, activity, and apical-basal polarization [269,270], and Wnt/planar cell polarity pathway components also seem to directly modulate actin dynamics [271]. Notably, an ancestral Wnt-like system in D. discoideum is responsible for actomyosin-mediated morphogenesis [272].…”
Section: Actomyosinmentioning
confidence: 99%